ROLE OF ICT IN SCIENCE EDUCATION FROM PRIMARY TO SECONDARY SCHOOL EDUCATION IN KERALA - Ranjusha.A; Dr. K.P.Meera (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Education plays a very dynamic role in changing the society and its needs. In this world of technology the teachers should acquire and update the technological skill so that they can reach up to the needs of a student of present era and fulfil it.The learning realm of today’s student is packed with computer and other gadgets. As this enhances their knowledge, the mastery over this becomes inevitable for the teacher trainers and the trained graduates.Then only the students of these teachers are benefitted out of it. It makes them more creative and scientific than the students of traditional class room. The total facet of society is being changed due to globalization and its demands are attained faster as the more techno-pedagogical skilled students work for it(Meera and Ranjusha,2016).ICT plays a very important role in the concept attainment of Science. ICT has improved pupils’ understanding of scientific concepts, hypothesis testing, developed problem solving skills, scientific relationships and process skills thereby improving their scientific reasoning. This is an era of technology, Technological innovations are being actuated in almost all realms of society. ICT can be considered as an important mode of scaffolding in every social domain.(Meera and Ranjusha,2016) This chapter is focused on the role of ICT enabled education in the field of science from primary to secondary school education in the context of Kerala.